1998
DOI: 10.1001/jama.279.4.287
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Paroxetine and Nortriptyline in Depressed Patients With Ischemic Heart Disease

Abstract: Context.-Depression and ischemic heart disease often are comorbid conditions and, in patients who have had a myocardial infarction, the presence of depression is associated with increased mortality. Patients with heart disease need a safe and effective treatment for depression. Objective.-To compare the efficacy, cardiovascular effects, and safety of a specific serotonin reuptake inhibitor, paroxetine, with a tricyclic antidepressant, nortriptyline hydrochloride, in depressed patients with ischemic heart disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
177
3
11

Year Published

1998
1998
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 413 publications
(195 citation statements)
references
References 32 publications
2
177
3
11
Order By: Relevance
“…6 The selective serotonin reuptake inhibitors (SSRIs) are well-established antidepressant drugs that have shown little evidence of cardiac toxicity, even in patients with stable heart disease. [7][8][9] However, no data on the safety or efficacy of SSRIs in either post-acute myocardial infarction (AMI) or unstable angina patients were available until the recent Sertraline AntiDepressant Heart Attack Randomized Trial (SADHART) of 364 depressed patients with ACSs. 10 The results of SADHART documented no evidence of harm with sertraline treatment.…”
mentioning
confidence: 99%
“…6 The selective serotonin reuptake inhibitors (SSRIs) are well-established antidepressant drugs that have shown little evidence of cardiac toxicity, even in patients with stable heart disease. [7][8][9] However, no data on the safety or efficacy of SSRIs in either post-acute myocardial infarction (AMI) or unstable angina patients were available until the recent Sertraline AntiDepressant Heart Attack Randomized Trial (SADHART) of 364 depressed patients with ACSs. 10 The results of SADHART documented no evidence of harm with sertraline treatment.…”
mentioning
confidence: 99%
“…All participants in this study had normal renal function. Type 2 diabetic patients taking tricyclic antidepressants were excluded as these medications are known to affect heart rate [7]. All routine blood parameters shown in this study were detected in the clinical laboratory of the University of Heidelberg using standardised and certified methods.…”
Section: Detection Of P75ntr Immunoreactivity In Plasma Samplesmentioning
confidence: 99%
“…4 All of the high-affinity SSRIs represented in the present study have been shown to reduce platelet aggregation. 5,[13][14][15] We know of no studies that have suggested altered platelet activity attributed to the other antidepressants with low or moderate serotonin transporter affinity; however, one study demonstrated no effect of nortriptyline on platelet activity. 14 If the mechanism of reducing MI is related to the effect of antidepressants on platelet serotonin, and if antidepressants in the higher-affinity groups have a greater antiplatelet effect than lower-affinity ones, then these drugs might be expected to have the greatest effect on MI risk.…”
Section: Potential Role Of Serotonin Reuptake Inhibitors In Preventiomentioning
confidence: 99%
“…5,[13][14][15] We know of no studies that have suggested altered platelet activity attributed to the other antidepressants with low or moderate serotonin transporter affinity; however, one study demonstrated no effect of nortriptyline on platelet activity. 14 If the mechanism of reducing MI is related to the effect of antidepressants on platelet serotonin, and if antidepressants in the higher-affinity groups have a greater antiplatelet effect than lower-affinity ones, then these drugs might be expected to have the greatest effect on MI risk. The potential effects of high serotonin transporter affinity antidepressants on platelet biology therefore form the basis for the a priori hypothesis that the extent of serotonin reuptake inhibition correlates with reduction in serotonin-mediated platelet aggregation and thus reduced risk of MI in users of these agents.…”
Section: Potential Role Of Serotonin Reuptake Inhibitors In Preventiomentioning
confidence: 99%
See 1 more Smart Citation